Preliminary Experimental Investigation on Autorotation Performance of Scale Model Helicopter in Vertical Manoeuvre - Wahab, A. A.; M. Ali, M. S. (2006)
This paper presents the results of the preliminary experimental investigation of reducing the steady rate of descent of a typical helicopter in vertical autorotation. Test data for two types of blades with different driving region areas were obtained. Results were summarized for zero collective pitch, same disk loading and same mass moment of inertia. The results of this preliminary test indicated that the expanding of the driving region area did reduce the steady rate of descent in vertical autorotation slightly and in agreement with the corresponding theoretical values. Further experimental investigation will be conducted looking for suitable driving region areas and collective pitch conditions that will give the reduction in the steady rate of descent significantly for ensuring safe landing condition.